(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A 45-year-old woman presented to us with generalized pruritus for the last 6 years. The itch was moderate in intensity causing interference with her daily activities and sleep. The pruritus was maximum in the evenings and there was no seasonal variation. It was not associated with any skin lesion. She did not have associated complaints of pain or altered sensation over the affected sites. She was a known case of diabetes mellitus and hypertension for the last 6- years which were moderately controlled with her medications. There was no history of atopy and any other systemic illnesses such as hypothyroidism or chronic liver and kidney diseases. There was a history of significant family stressors before the initiation of these episodes and aggravation of itch was noted with various stressors. The itch did not improve with her medications taken over the years such as antihistamines, antifungals, and antibiotics. Recently, she also started noticing palpitation and sweating associated with these episodes. The intensity of pruritus based on visual analogue scale was 7.